Collaborative Prescribing Practice in Managing Patients Post-Bariatric Surgery in a Tertiary Centre in Singapore - Giat Yeng Khee; Paik Shia Lim; Yoke Ling Chan; Phong Ching Lee (MDPI AG, 2024)
Background: A collaborative prescribing (CP) practice model, established by the endocrinologists, pharmacists, and advanced practice nurses, aims to provide for the postoperative monitoring and medical and nutritional management of stable patients after bariatric surgery. Method: Under the CP agreement, endocrinologists refer patients who have undergone bariatric surgery with stable medical conditions to CP practitioners, comprising senior pharmacists and advanced practice nurses. CP practitioners review the patient's weight loss progress, blood test results and vitals, the sufficiency of micronutrient repletion, adherence to supplements and medications, and chronic disease control. CP practitioners can prescribe and adjust the medications and supplements, in accordance with a clinical evaluation and standard guidance. Patients who require immediate attention due to complications or red flags are referred to the primary endocrinologist for further management. Results: From 5 May 2020 to 30 September 2023, CP practitioners provided 672 consultations. At least 68% and 80% of patients achieved appropriate weight loss post-surgery during the acute and maintenance phases, respectively. Less than 10% of the patients presented with anaemia and iron deficiency, and vitamin B12, folate and vitamin D deficiency. More than 80% of patients achieved a HbA1c of less than 7%. Conclusions: The CP practice framework provides a sustainable and viable model to facilitate optimal outcomes after bariatric surgery.